СТРАТЕГІЇ ЕФЕКТИВНОГО УПРАВЛІННЯ КОНФЛІКТНИМИ СИТУАЦІЯМИ В ОСВІТНЬОМУ СЕРЕДОВИЩІ - ПАПУТСІ, ВАСІЛІКІ (Наукові записки Тернопільського національного педагогічного університету імені Володимира Гнатюка. Серія: педагогіка, 2021)
The problem of communication among the participants of the educational environment occupies one of the leading places in modern pedagogical science. A natural possibility in an educational organization is the existence of conflict. This article presents the essential role of effective communication in the proper management of conflict within the school environment. It has been proved that dealing with conflicts in educational organizations executives tend to apply different styles of administrative behavior. These mainly include the integration of objectives, concession, enforcement, avoidance and compromise. The choice of conflict management-settlement style depends on organizational communication, the interdependence of individual objectives and the ability of individuals and groups to work together. The article analyses the specific type of communication the educational managers must rely on in order to achieve the collection of information, rational decision making and even the control of the expected results. Organizational communication is an important tool of effective management as executives manage to persuade, motivate and do what their subordinates want. It has been grounded that the crucial factor in effective conflict management through organizational communication is decision making. The article highlights the fact that the value of a conflict is assessed as favorable or not, depending on the participants in the conflict, the means used and the subjective criteria of the participants. The positive causes or constructive actions for the rational management of the conflict phenomenon must arise as a result of the dialectical way of dealing with disagreements, crises and conflicts. Their effective resolution is a positive potential for experience, as it provides an opportunity for stakeholders to get to know the problem, plan and implement positive changes in challenge outdated ways of thinking and develop new ways of working effectively together.